Zinc-philic hydrophobic interface modification layer of zinc metal negative electrode, preparation method and application
By forming a modified layer of interface on the surface of zinc metal negative poles on zinc -ion batteries and the formation of zinc metals and hydrophobic fluoride particles, it solves the growth of Zhi crystal, hydrogen analysis and side reaction on the interface of zinc ion batteries, and achieved zinc. High reversibility and long life of ion batteries.
Patent Information
- Application Number
- CN202411701438.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Zinc ion batteries have dendrite growth, hydrogen evolution reaction and side reaction problems at the zinc metal negative electrode/electrolyte interface, resulting in battery performance attenuation and short life.
Through the magnetic control sputtering technology, the nano -class -grade zinc metal and hydrophobic fluoride particles are splattered on the surface of the zinc metal negative surface, forming a dual -function nano -level interface modification layer, regulating the uniform deposition of zinc ions and inhibiting hydrogen analysis.
The uniform sedimentation and high reversibility of zinc metal's negative electrode, inhibit the hydrogen analysis and self -corrosion side effects, and improve the cycle life and Kuron efficiency of zinc ion batteries.
Smart Images

Figure CN119361591A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, and relates to a zinc-philic and hydrophobic interface modification layer of a zinc metal negative electrode, a preparation method and an application thereof. Background Art
[0002] Against the backdrop of global warming and the increasingly severe oil crisis, renewable energy, including solar energy, geothermal energy, wind energy, tidal energy, etc., is considered to be one of the most important energy sources for solving energy crises and environmental problems. However, the uneven distribution and deployment of renewable resources in time and space hinder their development in practical energy storage applications. Therefore, the development of large-scale electrochemical energy storage systems has very important social significance and economic benefits, and can make renewable energy a dispatchable and stable energy source. At present, lithium-based electrochemical systems are widely used in portable electronics, electric / hybrid vehicles, and grid energy storage equipment. However, the inherent problems of lithium-ion batteries, such as the shortage and high cost of battery materials and the flammability and explosiveness of organic electrolytes, severely limit their application in large-scale energy storage devices. Therefore, the search for electrochemical systems that can replace lithium-ion batteries has received widespread attention. Among them, aqueous zinc-ion batteries based on aqueous electrolytes have attracted much attention. Compared with standard hydrogen electrodes, metallic zinc (Zn) has a high conductivity of up to 820 mA h g -1 The theoretical capacity and the reduction potential as low as -0.76V, as well as its good natural abundance, make aqueous zinc-ion batteries (ZIBs) with zinc metal as the negative electrode have excellent safety performance, low economic cost and environmental friendliness, and have great potential to be used in large-scale grid energy storage equipment. However, zinc battery systems still face huge challenges: the dendrite growth of the core material zinc negative electrode, the hydrogen evolution reaction caused by the aqueous electrolyte, and the corrosion byproducts generated by the local alkalinity caused by this, all of which will cause the battery performance to decay or even fail. At present, it has become an urgent need in the field of aqueous zinc electricity to achieve uniform zinc deposition on the surface of the zinc metal negative electrode, inhibit the hydrogen evolution reaction and reduce side reactions, and achieve a stable zinc deposition / deposition cycle at the electrode / electrolyte interface to achieve an ultra-long cycle life. Therefore, people tend to focus on studying how to improve the stability of the zinc metal negative electrode / electrolyte interface.
[0003] At present, a series of in-depth studies and discussions have been conducted at home and abroad on improving the stability of the zinc metal anode / electrolyte interface, which can be roughly divided into three directions: (1) constructing an in-situ SEI (solid electrolyte interface) film on the surface of the zinc anode through electrolyte additives; (2) forming an artificial SEI film on the surface of the zinc anode through interface engineering modification; (3) optimizing the electrode composition or structure. Among them, for the interface engineering modification strategy, many scholars have tried to deposit different artificial interface modification layers on the surface of the zinc metal anode through physical coating or chemical induction, such as conductive carbon interface, metal nanoparticle coating, and inorganic coating. These interface modification strategies have improved the dendrite growth and side reaction problems at the interface between the zinc metal anode and the electrolyte to a certain extent.
[0004] Although the existing modification methods have improved the operating performance of aqueous zinc-ion batteries from different angles to a certain extent, there are still some problems: (1) A single interface modification strategy can only solve one-sided problems and may even aggravate other interface problems; (2) Most zinc negative electrode interface modification strategies have the problem of poor controllability; (3) The mechanism research of interface strategy is still lacking.
[0005] Therefore, it is crucial to study the zinc metal anode / electrolyte interface from the perspective of microscopic mechanism and explore new adjustable interface modification layers to effectively improve the interface stability and enhance the long-term operating stability of zinc-ion batteries. Summary of the invention
[0006] The purpose of the present invention is to provide an effective and excellent zinc metal negative electrode / electrolyte interface modification strategy for aqueous zinc ion batteries based on interface engineering theory, and a preparation method thereof, as well as a zinc ion battery using the interface modification strategy. The method uses magnetron sputtering coating technology to co-sputter a nanometer-scale zinc-philic metal with a certain solubility in zinc element and hydrophobic fluoride particles that can inhibit the side reaction of hydrogen evolution on the surface of a zinc metal negative electrode sheet (Zn, 99.99%), thereby forming a bifunctional nanometer-scale interface modification thin layer with zinc affinity and hydrophobicity, changing the double electric layer structure of the zinc metal negative electrode / electrolyte interface, fundamentally regulating the uniform deposition of zinc ions while inhibiting the side reaction of hydrogen evolution, and realizing a highly reversible zinc metal negative electrode with a long cycle time through synergistic action, thereby improving the cycle life and coulomb efficiency of the aqueous zinc ion battery.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode, wherein the interface modification layer is an M-XF nanolayer constructed on the surface of the zinc metal negative electrode, wherein M in the M-XF nanolayer is a zinc-philic metal nanoparticle having solid solubility with zinc metal, and XF in the M-XF nanolayer is a hydrophobic fluoride nanoparticle; the thickness of the M-XF nanolayer is 20 to 500 nm;
[0008] Zinc-philic metal (M) particles that can evenly distribute the current density on the electrode surface to regulate the uniform deposition of zinc metal and hydrophobic fluoride (XF) particles that inhibit side reactions at the electrode interface. Nanoscale particles are evenly attached to both sides and one side of the positive and negative electrodes of an aqueous zinc battery to prepare a zinc metal electrode with a double-sided deposition modification layer for testing the electrochemical performance of a symmetrical battery, and a zinc metal negative electrode with a single-sided deposition modification layer for testing the electrochemical performance of a full battery. The element M, which has a certain solubility in zinc, is used as a component of the interface modification layer and can form a solid solution alloy with zinc and evenly distribute the electric field on the surface of the zinc negative electrode, thereby promoting uniform, dendrite-free zinc deposition. Fluorides with good hydrophobicity, corrosion resistance and excellent ionic conductivity are used as components of the interface modification layer.
[0009] Preferably, M in the M-XF nanolayer includes one or more of copper, silver, tantalum, bismuth, scandium, yttrium, titanium, zirconium, hafnium, niobium, chromium, molybdenum, technetium, nickel, aluminum, indium, tin and lead.
[0010] Preferably, the XF in the M-XF nanolayer includes one or more of lithium fluoride, cerium fluoride, lanthanum fluoride, praseodymium fluoride and iron fluoride.
[0011] Preferably, the thickness of the M-XF nanolayer is 50 to 200 nm.
[0012] The present invention also discloses a method for preparing a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode, which is used to prepare the above-mentioned interface modification layer; the preparation method comprises: co-sputtering and depositing a zinc-philic metal M and a hydrophobic fluoride XF on metallic zinc by radio frequency magnetron sputtering, wherein the target materials during sputtering are the zinc-philic metal M and the fluoride XF target materials.
[0013] Preferably, the purity of the metallic zinc is ≥99.99%, and the metallic zinc includes: zinc foil.
[0014] Preferably, the background vacuum degree during the RF magnetron sputtering process is 0.1×10 -4 Pa~9.9×10 -4 Pa, the working gas pressure is 0.40-0.50 Pa, the working bias voltage is 90 V, and the purity of the target material is ≥99.99%.
[0015] Preferably, during the RF magnetron sputtering process, the target distance is 8 to 12 cm, the sputtering temperature is 20 to 30° C., and the sputtering time is 2 to 10 min.
[0016] The present invention also discloses an application of a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode, wherein the application adopts the above-mentioned interface modification layer and is used to prepare an aqueous zinc ion battery. The aqueous zinc ion battery comprises: a positive electrode, a diaphragm, a negative electrode and an aqueous electrolyte, wherein the positive electrode comprises ammonium vanadate powder NH4V4O 10 The separator includes a glass fiber membrane, the negative electrode includes zinc metal after interface modification, and the electrolyte includes a zinc sulfate solution ZnSO4.
[0017] The preparation process of the positive electrode of the aqueous zinc ion battery comprises the following steps: dissolving 0.85g of ammonium metavanadate (NH4VO3, Aladdin, 99%) in deionized water, stirring in a water bath at 80°C for 40 minutes, and the color of the solution changes from white to light yellow; adding 0.85g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder to the ammonium metavanadate solution, continuing to stir in a water bath at 80°C for 30 minutes, and the color of the solution changes from white to light blue-green; pouring the solution into a 50ml high-pressure reactor, heating at 180°C for 8h, cooling, repeatedly washing with deionized water, and drying at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water with a mass fraction of 60%) were dissolved in isopropanol in a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a 316 stainless steel mesh and dried in an oven at 70°C overnight to obtain a positive electrode.
[0018] Preferably, the thickness of the separator is 0.5-0.8 mm; the concentration of zinc sulfate ZnSO4 in the electrolyte solution is 1-3 mol / L.
[0019] The beneficial effects of the present invention are:
[0020] 1. The surface of the modified zinc negative electrode of the present invention is co-sputtered with nano-scale metal M particles and XF particles by radio frequency power magnetron sputtering. Among them, metal M has good zinc affinity and can form a stable solid solution with zinc. Metal M homogenizes the current density distribution on the surface of the zinc negative electrode, and acts as a nucleation site to induce uniform deposition of zinc ions, forming a dendrite-free negative electrode / electrolyte interface. Another component XF nanoparticles in the modified layer have good hydrophobicity and corrosion resistance, and isolate the zinc metal negative electrode and free water molecules in an acidic electrolyte environment, thereby inhibiting the hydrogen evolution side reaction and self-corrosion side reaction at the zinc negative electrode / electrolyte interface. Therefore, the zinc-philic and hydrophobic bifunctional interface modification layer of the present invention induces uniform zinc deposition and inhibits side reactions such as hydrogen evolution on the electrode surface.
[0021] 2. The present invention regulates the composition of the dual-functional nano-particle modification layer through radio frequency co-sputtering technology to form an M-XF interface modification layer with a certain atomic ratio, so that the double electric layer structure on the surface of the zinc negative electrode is optimized, and uniform dendrite-free zinc ion deposition is achieved while isolating the free water molecules in the double electric layer on the surface of the zinc negative electrode, thereby inhibiting side reactions. Therefore, the present invention improves the reversibility and stability of the zinc metal negative electrode, improves the coulombic efficiency and cycle stability of the zinc ion battery, and reduces its capacity attenuation.
[0022] 3. The present invention forms a metal M nanoparticle modification layer doped with a small amount of XF nanoparticles and having a certain solid solubility with zinc on the surface of the zinc negative electrode through radio frequency magnetron sputtering co-sputtering; therefore, the present invention realizes a uniform and dense modified nanoparticle modification layer, inducing uniform deposition of zinc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The invention discloses a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode, a preparation method and an application thereof. The zinc electrode assembled with the nano Ag-LiF interface modification layer has a current density of 5 mA cm -2 Cyclic stability diagram when ;
[0024] Figure 2 This is a graph of the cycle stability of a zinc symmetric battery assembled with a zinc electrode having a nano Ag-LiF interface modification layer introduced into the present invention when different current densities are changed;
[0025] Figure 3 The graph is a cycle stability diagram of a full battery assembled with a zinc metal negative electrode introduced with a nano-Ag-LiF modified layer and an ammonium vanadate positive electrode at different rates. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] refer to Figures 1 to 3, the interface modification layer prepared by co-sputtering by magnetron sputtering method and the optimized zinc metal negative electrode based on this modification layer in this embodiment. The modification layer is co-sputtered by radio frequency to uniformly deposit zinc-philic metal (M) nanoparticles with a certain solid solubility with zinc metal and hydrophobic fluoride (XF) nanoparticles on a high-purity zinc foil (Zn≥99.99%) substrate. Among them, the zinc-philic metal M can induce the uniform deposition of zinc ions on the zinc electrode, inhibit the growth of zinc dendrites, and prevent capacity decay and even short circuit caused by dendrites piercing the diaphragm; the hydrophobic fluoride XF can reduce the amount of free water on the surface of the zinc metal negative electrode, thereby inhibiting the occurrence of hydrogen evolution reaction and preventing the performance impact or even failure caused by battery bulging; at the same time, the co-sputtered multifunctional modification layer acts as a physical shielding layer to prevent direct contact between the zinc negative electrode and the electrolyte, and inhibit various interface side reactions.
[0028] The aqueous zinc battery structure used in the zinc negative electrode based on the multifunctional modified layer also includes a positive electrode, a separator and an electrolyte. Among them, the positive electrode is a stainless steel mesh attached with ammonium vanadate, the separator is a glass fiber membrane, the electrolyte is a zinc sulfate solution, and the side of the zinc metal with the multifunctional modified layer attached faces the separator.
[0029] The specific preparation steps of the aqueous zinc ion battery formed by assembling the zinc metal negative electrode with the multifunctional modified layer include:
[0030] Step 1, cut a 0.05 mm thick high-purity zinc foil (Zn ≥ 99.99%), clean it with alcohol and dry it;
[0031] Step 2, fix the zinc foil prepared in step 1 on the magnetron sputtering sample plate with conductive tape, clean the sample with alcohol using a cotton swab and dry it thoroughly; fix the sample plate containing the zinc foil in the chamber of the magnetron sputtering equipment and cover it with a baffle; polish the selected target material (purity ≥ 99.99%) with sandpaper, then clean it with alcohol and dry it thoroughly; after the chamber is evacuated to the background vacuum, pre-sputter the target material for five minutes to clean the surface impurities and oxides to ensure the purity of the modified layer; after pre-sputtering, adjust the vacuum to the working pressure, open the sample baffle for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum (0.1~9.9)×10 -4 Pa, working gas pressure is 0.4-0.5Pa, target distance is 8-12cm, sputtering bias voltage is ~90V, sputtering power is optimized according to different target materials, sputtering temperature is 20-30℃, sample disk speed is 16rpm, sputtering time is 1-10min;
[0032] Step 3, under the preferred magnetron sputtering process of step 2, two substances: metal M and fluoride XF are deposited simultaneously by radio frequency power supply to obtain a zinc foil with a 50-200nm nano-modified layer, which is cut by a tablet press and used as a negative electrode of the battery;
[0033] Step 4, preparation of the separator: cutting a glass fiber film with a thickness of 0.68 mm with a tablet press to use as a battery separator;
[0034] Step 5, preparation of ammonium vanadate positive electrode: 0.85g ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85g oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and continued to stir in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50ml high-pressure reactor, heated at 180°C for 8h, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water with a mass fraction of 60%) were dissolved in isopropanol in a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh and dried in an oven at 70°C overnight to obtain a positive electrode.
[0035] Step 6, preparation of electrolyte solution: dissolving zinc sulfate heptahydrate (Aladdin, 99.995%) powder in deionized water to obtain an electrolyte solution with a concentration of 2 mol / L;
[0036] Step 7, assembly of ammonium vanadate / modified zinc metal full battery: at room temperature, place the modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode into a standard CR2032 button battery shell, drip 100 μL electrolyte on both sides of the diaphragm, and assemble the full battery using a button battery sealing machine. The zinc metal negative electrode modified layer faces the glass fiber diaphragm.
[0037] The prepared full battery was subjected to charge and discharge performance tests and cycled at different rates in the range of 0.1-3A / g at 26°C, with the test voltage range of 1.2V to 2.0V for each cycle.
[0038] Example 1
[0039] Prepare a zinc metal anode with an Ag-LiF multifunctional modified layer and apply it to aqueous zinc ion full batteries;
[0040] The cleaned and dried high-purity zinc foil (Zn ≥ 99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Ag target and LiF target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Ag-LiF modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum degree 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0041] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0042] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0043] The battery prepared in the comparative example and in Example 1 was subjected to charge and discharge comparison tests. It was found that after the multifunctional modified layer proposed in this embodiment was introduced into the zinc metal negative electrode, the current density was 5 mA cm -2 The cycle stability, reversibility and cycle life of the assembled zinc symmetric battery were greatly improved; the reversibility and stability of the assembled ammonium vanadate / zinc metal full battery were improved in different rate cycles at 26°C, and the capacity retention rate was as high as 97% after 45 cycles at different rates.
[0044] Example 2
[0045] Prepare a zinc metal anode with a Cu-LiF multifunctional modified layer and apply it in aqueous zinc ion full batteries;
[0046] The cleaned and dried high-purity zinc foil (Zn ≥ 99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Cu target and LiF target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Cu-LiF modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0047] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0048] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0049] Example 3
[0050] Prepare a zinc metal anode with a Ta-LiF multifunctional modified layer and apply it in aqueous zinc ion full batteries;
[0051] The cleaned and dried high-purity zinc foil (Zn ≥ 99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Ta target and LiF target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Ta-LiF modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0052] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0053] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0054] Example 4
[0055] Preparation of zinc metal anode with Bi-LiF multifunctional modified layer and its application in aqueous zinc ion full battery;
[0056] The cleaned and dried high-purity zinc foil (Zn ≥ 99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Bi target and LiF target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Bi-LiF modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0057] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0058] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0059] Example 5
[0060] Prepare zinc metal anode with Ag-ZnF2 multifunctional modified layer and apply it in aqueous zinc ion full battery;
[0061] The cleaned and dried high-purity zinc foil (Zn≥99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Ag target and ZnF2 target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Ag-ZnF2 modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum degree 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0062] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0063] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0064] Example 6
[0065] Preparation of zinc metal anode with Cu-ZnF2 multifunctional modified layer and its application in aqueous zinc ion full battery;
[0066] The cleaned and dried high-purity zinc foil (Zn≥99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The 99.99% pure Cu target and ZnF2 target were sanded, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Cu-ZnF2 modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0067] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0068] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0069] Example 7
[0070] Prepare zinc metal anode with Ta-ZnF2 multifunctional modified layer and apply it in aqueous zinc ion full battery;
[0071] The cleaned and dried high-purity zinc foil (Zn≥99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Ta target and ZnF2 target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Ta-ZnF2 modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum degree 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0072] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0073] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0074] Example 8
[0075] Preparation of zinc metal anode with Bi-ZnF2 multifunctional modified layer and its application in aqueous zinc ion full battery;
[0076] The cleaned and dried high-purity zinc foil (Zn≥99.99%) was fixed on the magnetron sputtering sample plate with conductive tape, loaded into the sputtering chamber and covered with a baffle. The Bi target and ZnF2 target with a purity of 99.99% were polished with sandpaper, cleaned with alcohol and dried, and then pre-sputtered for five minutes to clean the surface oxides and irrelevant impurities to ensure the purity of the Bi-ZnF2 modified layer; after the pre-sputtering, the sample baffle was opened for co-sputtering. The process parameters of RF magnetron sputtering are: background vacuum degree 6.0×10 -4 Pa, the working gas pressure after introducing 99.99% purity argon is 0.45Pa, the target distance is 10cm, the sputtering bias is ~90V, the sputtering power is 80W, the sputtering temperature is 26℃, the sample disk speed is 16rpm, and the sputtering time is 1min.
[0077] 0.85 g of ammonium metavanadate (NH4VO3, Aladdin, 99%) was dissolved in deionized water, stirred in a water bath at 80°C for 40 minutes, and the color of the solution changed from white to light yellow; 0.85 g of oxalic acid (H2C2O4·2H2O, Aladdin, 99%) powder was added to the ammonium metavanadate solution, and the solution was stirred in a water bath at 80°C for 30 minutes, and the color of the solution changed from white to light blue-green; the solution was poured into a 50 ml high-pressure reactor, heated at 180°C for 8 hours, cooled, repeatedly washed with deionized water, and dried at room temperature overnight to obtain ammonium vanadate NH4V4O 10 Powder; NH4V4O 10 Powder, Ketjen black (KB) and polytetrafluoroethylene (PTFE, dispersed in water at a mass fraction of 60%) were dissolved in isopropanol at a mass fraction ratio of 75:15:10 to form a mixture; the mixture was cast on a cut 316 stainless steel mesh, dried in an oven at 70°C overnight and cut to obtain a positive electrode.
[0078] The modified zinc metal negative electrode, glass fiber membrane, and ammonium vanadate positive electrode were placed in a standard CR2032 button battery shell, and 100 μL of 2 mol / L zinc sulfate electrolyte was dripped on both sides of the diaphragm. The full battery was assembled using a button battery sealing machine. The zinc metal negative electrode modified layer faced the glass fiber diaphragm.
[0079] This embodiment is at 26°C, 5 mA cm -2 The constant current cycle curve under high current density is as follows: Figure 1 As shown in the figure, compared with the control sample with an overpotential of ~80mV, the modified symmetric battery has a stable overpotential of ~50mV, and the operating stability and cycle stability are significantly improved, and can operate stably for more than 1000 hours. Figure 2As shown in the figure, the operating current density of the symmetrical battery is changed to 1, 2, 3, 5, 10, and then gradually reduced to characterize the rate performance of the battery. The modified battery shows good cycle stability and reversibility, while the control sample fails midway.
[0080] In this embodiment, the zinc negative electrode with the M-XF interface modification layer and the ammonium vanadate positive electrode are assembled into a full battery, which is operated at different current densities in turn, such as Figure 3 As shown, the ammonium vanadate / M-XF interface modified layer zinc metal battery has good capacity retention and good cycle performance, and maintains a high discharge capacity after the current density changes back to 0.1 A / g.
[0081] The principle of the M-XF interface modification layer in this embodiment to improve the operating stability and reversibility of symmetrical batteries and full batteries is as follows: 1) the zinc-philic nanometal M uniformly deposited in the modification layer can form a solid solution with zinc, which homogenizes the current density distribution on the surface of the zinc electrode, induces uniform deposition of zinc, and inhibits dendrite growth; 2) the fluoride (XF) nanoparticles in the modification layer are hydrophobic, which reduces the amount of free water in the double layer and inhibits the hydrogen evolution reaction; 3) the introduction of the multifunctional modification layer forms a protective layer on the surface of the zinc electrode, reducing the side reactions caused by direct contact between zinc metal and the electrolyte in the double layer.
[0082] The ultimate goal of this embodiment is to improve the uneven zinc dendrite growth at the interface between the zinc electrode and the electrolyte, and to inhibit the side reactions such as hydrogen evolution reaction and self-corrosion at the interface. Therefore, this embodiment introduces a multifunctional zinc-philic hydrophobic modification layer at the zinc negative electrode / electrolyte interface, which is uniformly compounded by nano-scale metal M and fluoride XF. Among them, metal M can form a solid solution with a certain solid solubility with zinc, and the uniform zinc-philic metal M at the interface can induce uniform zinc deposition, thereby inhibiting the growth of zinc dendrites; hydrophobic fluoride (XF) particles can reduce the free water molecules at the zinc negative electrode / electrolyte interface, thereby inhibiting the hydrogen evolution reaction; at the same time, the multifunctional modification layer acts as a physical barrier layer to hinder the direct contact between zinc metal and the electrolyte, and inhibits the generation of interface side reactions such as self-corrosion. The introduction of this multifunctional modification layer improves the stability and reversibility of the zinc negative electrode, and has been proven to improve the battery performance and life in practical applications.
[0083] In summary, the present invention co-sputters nano-scale metal M particles and XF particles on the surface of the modified zinc negative electrode by magnetron sputtering with a radio frequency power supply. Among them, metal M has good zinc affinity and can form a stable solid solution with zinc. Metal M homogenizes the current density distribution on the surface of the zinc negative electrode, and acts as a nucleation site to induce uniform deposition of zinc ions, forming a dendrite-free negative electrode / electrolyte interface. Another component XF nanoparticles in the modified layer have good hydrophobicity and corrosion resistance, and isolate the zinc metal negative electrode and free water molecules in an acidic electrolyte environment, thereby inhibiting the hydrogen evolution side reaction and self-corrosion side reaction at the zinc negative electrode / electrolyte interface. Therefore, the zinc-philic and hydrophobic dual-functional interface modification layer of the present invention induces uniform zinc deposition and inhibits side reactions such as hydrogen evolution on the electrode surface.
[0084] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A zinc-philic hydrophobic interface modification layer for a zinc metal negative electrode, characterized in that: The interface modification layer is an M-XF nanolayer constructed on the surface of the zinc metal negative electrode, wherein the M in the M-XF nanolayer is a zinc-philic metal nanoparticle having a solid solubility with zinc metal, and the XF in the M-XF nanolayer is a hydrophobic fluoride nanoparticle; the thickness of the M-XF nanolayer is 20 to 500 nm.
2. The zinc-philic and hydrophobic interface modification layer of a zinc metal negative electrode according to claim 1, characterized in that: The M in the M-XF nanolayer includes one or more of copper, silver, tantalum, bismuth, scandium, yttrium, titanium, zirconium, hafnium, niobium, chromium, molybdenum, technetium, nickel, aluminum, indium, tin, and lead.
3. The zinc-philic and hydrophobic interface modification layer of a zinc metal negative electrode according to claim 1, characterized in that: The XF in the M-XF nanolayer includes one or more of lithium fluoride, cerium fluoride, lanthanum fluoride, praseodymium fluoride and iron fluoride.
4. The zinc-philic and hydrophobic interface modification layer of a zinc metal negative electrode according to claim 1, characterized in that: The thickness of the M-XF nanolayer is 50 to 200 nm.
5. A method for preparing a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode, characterized in that: The preparation method is used to prepare the interface modification layer described in any one of claims 1 to 4; the preparation method comprises: co-sputtering and depositing the zinc-philic metal M and the hydrophobic fluoride XF on metallic zinc by radio frequency magnetron sputtering, wherein the target materials during sputtering are the zinc-philic metal M and the fluoride XF target materials.
6. The method for preparing a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode according to claim 5, characterized in that: The purity of the metallic zinc is ≥99.99%, and the metallic zinc includes: zinc foil.
7. The method for preparing a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode according to claim 5, characterized in that: The background vacuum degree during the RF magnetron sputtering process is 0.1×10 -4 Pa~9.9×10 -4 Pa, the working gas pressure is 0.40-0.50 Pa, the working bias voltage is 90 V, and the purity of the target material is ≥99.99%.
8. The method for preparing a zinc-philic hydrophobic interface modification layer of a zinc metal negative electrode according to claim 5, characterized in that: In the radio frequency magnetron sputtering process, the target distance is 8 to 12 cm, the sputtering temperature is 20 to 30° C., and the sputtering time is 2 to 10 minutes.
9. An application of a zinc-philic hydrophobic interface modification layer for a zinc metal negative electrode, characterized in that: The application adopts the interface modification layer described in any one of claims 1 to 4, and the application is used to prepare an aqueous zinc ion battery, wherein the aqueous zinc ion battery comprises: a positive electrode, a diaphragm, a negative electrode and an aqueous electrolyte, wherein the positive electrode comprises ammonium vanadate powder NH4V4O 10 The separator includes a glass fiber membrane, the negative electrode includes zinc metal after interface modification, and the electrolyte includes a zinc sulfate solution ZnSO4.
10. The use of a zinc-philic hydrophobic interface modification layer for a zinc metal negative electrode according to claim 9, characterized in that: The thickness of the diaphragm is 0.5-0.8 mm; the concentration of zinc sulfate ZnSO4 in the electrolyte solution is 1-3 mol / L.
Citation Information
Patent Citations
Corrosion-inhibiting zinc powder used for alkaline manganese battery and preparation process for corrosion-inhibiting zinc powder
CN109735815A
Preparation method of aqueous corrosion-resistant dendritic-crystal-free metal negative electrode
CN111312984A
Fluoride surface modified secondary battery carbon negative electrode material and preparation method thereof
CN112786862A
Preparation method of high-cycle-stability secondary zinc battery negative electrode aluminum-zinc alloy coating
CN114094035A
Double-phase interface protected metal zinc negative electrode and preparation method and application thereof
CN114551775A
Cited By
Hydrophobic-zinc-philic interface protection layer of high-magnification zinc metal negative electrode as well as preparation and application of hydrophobic-zinc-philic interface protection layer
CN120388990A